Bathymetric map of Lago Fagnano (Tierra del Fuego Island) - Zanolla, C. (2011)
We present a general bathymetric map of Lago Fagnano, the largest ice-free lake of the Southern Hemisphere, located in the central part of the Tierra del Fuego Island. The map has been obtained compiling all the available bathymetric soundings and depth-converted high-resolution seismic profiles, collected in the course of several geophysical campaigns. The lake occupies a 110-km long, E-W trending tectonic depression within the southernmost tip of the Andean Cordillera, where the South America-Scotia plate boundary traverses the Tierra del Fuego Island. The map allows us to identify the main morpho-bathymetric features of Lago Fagnano. The lake floor is divided into two principal sectors of different water depths, separated by a main shoal located in the central part of the lake. Maximum water depth (206 m) is found in the eastern part, whereas water depths in the western half do not exceed 165 m. In this paper, we describe the geometry and the general morphological characteristics of the basin, which was generated by a combination of distinct tectonic processes, and later superposed by Late Quaternary glacial and glacio-lacustrine dynamic events.